Behavioral Disturbances among School Children in Baghdad Province - hussain, Sulaf A .; M, Maliha; Wahid, Salwa S. A. (AL-Kindy College Medical Journal, 2009)
Background: Mental health of children has recently beenreceiving increased attention in many parts of the world.However, such attention has been lacking in developingcountries, particularly in the form of systematic researchAim: The study aimed to find out the frequency ofbehavior disorders in a sample of primary school childrenand the different social and demographic factors that mightbe related to this disorder.Methods: The study is a cross-sectional one that included918 primary school pupils in both urban and rural areas ofBaghdad. Rutter's questionnaire teacher's version was usedto assess the pupils, and the demographic data was obtainedby special questionnaire sent to the parents to becompleted.Results: The rate of behavior disorder was found to be49%, in both rural and urban areas, males had higherprevalence rate than females. The disturbed pupils hadhigher scholastic failure and their parents of lowereducational level and came from highly crowded houses,they had higher rate of disrupted family by either death ofone of the parents or their father is married to more thanone wife.Conclusion: There is high rate of behavior disturbances inschool aged children in Baghdad, associated with lowsocioeconomic status, bereaved children and having fathersmarried to more than one wife. The study shows that thesechildren have low scholastic achievement.